A Noise Removal Algorithm of Color Image - WANG Jianwei (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
An algorithm of the color image noise removal algorithm is put forward based on the pixel operations. The idea of the algorithm is to read every pixel in a set order and determine whether the pixel level is consistent with the probability density function of impulse noise or not. If it is similar to noise pixel, the number of impulse noise in a certain mask is counted. If the number is less than the given threshold, the pixel is considered as possible noise. The pixel value is not unchanged. Otherwise it is considered as noise, the result mask operation of the pixel is to replace the pixel value. Otherwise it isn’t considered as noise, the pixel value is also unchanged. The experimental results show that the algorithm is applicable to the gray noisy image and the color noisy image.It has the advantages of higher speed and more stable noise removal effects.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3054